Current trends analysis and prioritization of success factors: a systematic literature review of ICT projects. Issue 3 (6th August 2020) - Ayat, Muhammad; Imran, Muhammad; Ullah, Azmat; Kang, Chang Wook
Abstract : Purpose: The purpose of this study is to investigate the current literature that has explored project success in the information and communication technology (ICT) sector. Design/methodology/approach: The literature search was carried out for related articles in three databases: the Web of Science, Scopus and Ebscohost. Using a systematic literature review (SLR) methodology, 75 related articles were sorted out. Furthermore, the methods of frequency and content analysis were used to identify, categorize and arrange critical success factors (CSF) of ICT projects based on their importance, interrelation and cultural regions. Findings: The findings in this study revealed that interest in researching success in ICT projects has increased significantly during the last five years. Through reviewing the selected articles, 25 CSF were identified. User participation, stakeholder relationship, project manager emotional intelligence, communication skills, and leadership skills, and top management support in the project emerged as the most important factors for ICT projects. Furthermore, we found that each regional group gives different level of importance to different CSF. Practical implications: This study gives the opportunity to practitioners to control the highest value CSF to increase the success rate of ICT projects carried out in different cultural regions. Originality/value: As the first study of its type, CSF were divided for different cultural regional groups. This paper further explained that certain CSF have different levels of importance in different culture regions. This study suggests that regional culture needs consideration during the evaluation of CSF.